Metabolic Syndrome and Autophagy: Focus on HMGB1 Protein - Frisardi, Vincenza; Matrone, Carmela; Street, Maria Elisabeth (Frontiers in Cell and Developmental Biology, 2021)
Metabolic syndrome (MetS) affects the population worldwide and results from several factors such as genetic background, environment and lifestyle. In recent years, an interplay among autophagy, metabolism and metabolic disorders has become apparent. Defects in the autophagy machinery are associated with the dysfunction of many tissues/organs regulating metabolism. Metabolic hormones and nutrients regulate, in turn, the autophagy mechanism. Autophagy is a housekeeping stress-induced degradation process that ensures cellular homeostasis. High mobility group box 1 (HMGB1) is a highly conserved nuclear protein with a nuclear and extracellular role that functions as an extracellular signaling molecule under specific conditions. Several studies have shown that HMGB1 is a critical regulator of autophagy. This mini-review focuses on the involvement of HMGB1 protein in the interplay between autophagy and MetS, emphasizing its potential role as a promising biomarker candidate for the early stage of MetS or disease's therapeutic target.